Evaluation of integrated inverter topologies for low power PV systems - Junior, Luigi G.; De Brito, Moacyr A. G.; Sampaio, Leonardo P.; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This work presents the stage integration in power electronics converters as a suitable solution for solar photovoltaic inverters. The rated voltages available in Photovoltaic (PV) modules have usually low values for applications such as regulated output voltages in stand-alone or grid-connected configurations. In these cases, a boost stage or a transformer will be necessary. Transformers have low efficiencies, heavy weights and have been used only when galvanic isolation is mandatory. Furthermore, high-frequency transformers increase the converter complexity. Therefore, the most usual topologies use a boost stage and one inverter stage cascaded. However, the complexity, size, weight, cost and lifetime might be improved considering the integration of both stages. These are the expected features to turn attractive this kind of integrated structures. Therefore, some integrated converters are analyzed and compared in this paper in order to support future evaluations and trends for low power single-phase inverters for PV systems. © 2011 IEEE.
Keywords: Low-Power Inverters; Photovoltaic Modules; Single-phase Solar Inverters; Stage Integration; Galvanic isolation; Grid-connected; Integrated converters; Integrated inverter; Integrated structure; Inverter stage; Low Power; Output voltages; Photovoltaic modules; Power electronics converters; PV system; Rated voltages; Single-phase inverters; Solar inverter; Solar photovoltaics; Suitable solutions; Electric inverters; Energy resources; High frequency transformers; Photovoltaic effects; Power electronics; Solar energy; Solar power generation; Topology; Integration